Cognitive Language Aptitude. (25th September 2018) - Doughty, Catherine J.
Abstract: After discussing key issues in the aptitude literature and presenting an updated, multicomponential model of cognitive language aptitude, we consider two analyses from a longitudinal investigation using aptitude to predict success in language learning. Aptitude is conceptualized as a special talent for learning languages and a ceiling on success. In other words, for any given person, when motivation is high, personality facets are aligned, and the learning context is excellent, differences in aptitude determine ultimate attainment. Findings show that the full Modern Language Aptitude Test and the full High‐Level Language Aptitude Battery each predicted adult language learning success outcomes. In addition, different combinations of components drawn from these two (by design) complementary aptitude batteries predicted different aspects of basic and advanced proficiency and did so above and beyond nonaptitude variables, such as childhood exposure, previous language learning, age at the time of training, level of education, and enjoyment.